Gene and Enhancer Trap Transposable Elements Reveal Oxygen Deprivation‐regulated Genes and their Complex Patterns of Expression in Arabidopsis - BAXTER‐BURRELL, AIRICA (Ann Bot, 2003)
Transposon tagging with modified maize Ds–GUS constructs was used to isolate genes induced by oxygen deprivation in Arabidopsis thaliana. Seedlings of 800 gene‐trap (DsG) and 600 enhancer‐trap (DsE) lines were grown on vertically positioned plates for 1 week, oxygen deprived for up to 24 h and stained for GUS activity. Oxygen deprivation induced intricate patterns of gene expression in seedlings of 65 lines. The insertion site and phenotypes of 15 lines were examined. Surprisingly, none of the insertions were into genes that encode known anaerobic polypeptides. Insertions were identified within or adjacent to genes encoding proteins of regulatory, enzymatic, mitochondrial protein import and unknown function, as well as adjacent to genes encoding a putative receptor‐like kinase and putative sensor‐histidine kinase. Four lines had significantly lower ADH activity after 24 h of oxygen deprivation and three of these showed reduced stress tolerance. Two lines with wild‐type levels of ADH were low‐oxygen intolerant. Paradoxically, several lines had significantly higher ADH activity after 12 h of oxygen deprivation but reduced stress tolerance. Caffeine treatment, which increased ADH specific activity in wild‐type seedlings under aerobic conditions, was sufficient to increase GUS staining in seven of the 15 lines, providing evidence that these genes may be regulated by cytosolic calcium levels. These results demonstrate the effectiveness of the Ds–GUS tagging system in the identification of genes that are regulated in response to oxygen deprivation and a calcium second messenger.